Ligand-gated ion channel P2X7 regulates hypoxia-induced factor-1α mediated pain induced by dental pulpitis in the medullary dorsal horn - Zhang, Jing; Si, Jialin; Liang, Rongrong; Lu, Yuxin; Shang, Hongwei; Li, Xinwei; Sun, Shukai; Wu, Li-an (Frontiers in Molecular Neuroscience, 2022)
Dental pulpitis often induces severe pain, and the molecular immune response is remarkable in both peripheral and central nervous system. Accumulating evidence indicates that activated microglia in the medullary dorsal horn (MDH) contribute to dental pulpitis induced pain. The P2X7 receptor plays an important role in driving pain and inflammatory processes, and its downstream target HIF-1α has a crucial role in maintaining inflammation. However, the relationship between P2X7 and HIF-1α in dental inflammatory pain remains unclear. This study demonstrated that the degree of inflammation in the dental pulp tissue became more severe in a time-dependent manner by establishing a rat dental pulpitis model via pulp exposure. Meanwhile, the expression of P2X7, HIF-1α, IL-18, and IL-1β in the MDH increased most on the 7th day when the pain threshold was the lowest in the dental pulpitis model. Furthermore, lipopolysaccharides (LPS) increased P2X7-mediated HIF-1α expression in microglia. Notably, the suppression of P2X7 expression caused less IL-1β and IL-18 release and lower HIF-1α expression in vitro experiments. In conclusion, our results provide further evidence that P2X7 is a key molecule which regulates HIF-1α expressionand inflammation in dental pulpitis-induced pain.